Structural Example-Oriented Tutoring System - MUSTAFA, MIRWAN ASHRAN (universiti teknologi petronas, 2005)
Structural Example-Oriented Tutoring System is a web-based tutoring system that uses examples as the main form of knowledge management that is structured to the level of the difficulties. The objective of this project is primarily to develop the system by implementing the structural and example-oriented tutorial concept. The scope of study for this project is generally down to the course of developing the system, including research about the system and the subject that the system is tutoring for. The intended user for this system is for UTP students who are taking Introduction to Finance subject. The methodology used for developing the system is an evolutionary approach, which followed five main processes namely project identification, requirement analysis, system specification, system development and system testing. The finished product will hopefully be used in the market, uploaded to a host site for users to access through the internet. Side by side with the traditional tutoring system, the system will complement the current system in helping the process of learning the subject matter for the users.